Jejak Bahasa dalam Papan Nama: Lanskap Linguistik pada Kursus dan Pelatihan di Kota Malang - Lina Yuliasari; Millatuz Zakiyah (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2026)
The signboards of course and training institutions represent the identity and image of their speakers. This study aims to uncover the forms and patterns of language use, examine the informational and symbolic functions, as well as the social aspects that emerge from language use on the signboards of course and training institutions in the city of Malang. This qualitative study employs a linguistic landscape approach using the theory of Landry and Bourhis. The data sources refer to documentation of 114 signboards from course and training institutions across five sub- districts (Klojen, Lowokwaru, Blimbing, Sukun, and Kedungkandang) in Malang through field observations conducted in October 2025. The data consist of texts on the signboards in the form of words, phrases, and clauses. Data collection was carried out using the note-taking observation technique. Data analysis was conducted using the linguistic landscape framework of Landry and Bourhis. The data was analyzed through the stages of (1) classifying the data; (2) identifying informational and symbolic functions; (3) tracing the emerging social aspects. The findings show a dominance of bilingual language (60.5%), followed by monolingual (28.9%) and multilingual (10.5%), indicating the use of foreign language as symbolic capital and the marginalization of local identity. Information is dominated by business names (113), addresses (64), and contacts (72), highlighting ease of access. Social aspects are emphasized by social status, followed by age, gender, religion, ethnicity, and geography, reflecting the institution's existence as a symbol of aspirations for social mobility.